Defguard Implementation for Remote Access Management Using WireGuard VPN at PT. Esta Dana Ventura - Bany, Ervan Jefferson; Hadi Arfian, Muhamad (Universitas Islam Kuantan Singingi, 2025)
This study examines the development and deployment of a remote access management system by integrating Defguard with the WireGuard VPN at PT. Esta Dana Ventura. The company previously faced unstable connections and inefficient user administration due to the limitations of its MikroTik-based PPTP and L2TP VPN solutions. To overcome these challenges, a new architecture was designed using WireGuard for its lightweight performance and Defguard for centralized and streamlined access control. The system was implemented within a Docker environment and evaluated using key performance indicators such as latency, throughput, packet loss, and connection stability across multiple internet service providers. The results demonstrated that the WireGuard-based configuration delivered lower latency, zero packet loss, and secure connections without DNS leakage, while token-based authentication significantly simplified user management. Overall, the new system enhanced connection reliability, improved security, and provided scalable remote access for geographically distributed users, making it an effective replacement for the legacy VPN infrastructure.